Fatty Acid Profile and Metabolism Are Related to Human Sperm Parameters and Are Relevant in Idiopathic Infertility and Varicocele - Giulia Collodel; Elena Moretti; Daria Noto; Francesca Iacoponi; Cinzia Signorini (Mediators of Inflammation)
Objectives. Fatty acids (FA) modulate oxidative stress, reactive oxygen species (ROS) production, and inflammatory processes in spermatogenesis. Methods. The amount of 17 different FAs and the level of F2-isoprostanes (F2-IsoPs) and cytoplasmic phospholipase A2 (cPLA2) were compared and correlated to sperm characteristics; these last ones were evaluated by light and electronic microscopy in varicocele and idiopathic infertile patients. Results. Total n-3 polyunsaturated acids (PUFAs) and docosahexaenoic acid (DHA), one of the n-3 PUFAs, were significantly reduced in idiopathic infertile men compared to controls (P<0.05). In the whole studied population, oleic acid and total monounsaturated acids (MUFAs) correlated negatively with sperm concentration, progressive motility, normal morphology, vitality, and fertility index and positively with sperm necrosis. Eicosapentaenoic acid (EPA) amount was positively correlated with the percentage of sperm necrosis and cPLA2 level and negatively with sperm concentration. Sperm vitality was negatively correlated with the saturated fatty acids (SFAs). In infertile groups, cPLA2 was negatively correlated with DHA and n-3 PUFAs (both P<0.05) and positively with EPA (P<0.05). In the varicocele group, sperm vitality was negatively correlated with palmitoleic acid and total n-6 PUFAs (P<0.05); sperm apoptosis was positively correlated with the total SFA percentage (P<0.05). Conclusions. FA composition in sperm membrane and the metabolism of sperm FAs are interrelated parameters, both relevant in sperm maturation processes and fertility.